Empowered Voices: The Experiences of Left-Behind Women in Rural Morocco - Lamiae, Fadili; Raja, Rhouni; Mohammed, Derdar (Integrated Journal for Research in Arts and Humanities, 2024)
Our comprehensive interviews and observational research highlight a crucial disparity between established theories of empowerment, such as those by Naila Kabeer, and the perspectives of left-behind women in rural Morocco. This gap underscores the need to bridge academic discourse with the real-life experiences of these women. Our study aims to develop a theoretical framework that explains these differences, emphasizing previously overlooked factors. Specifically, our findings reveal the significant role of family ties and the importance of creating an environment for dignified living—elements often marginalized in empowerment discussions. This nuanced understanding is essential for evolving the concept of empowerment to better reflect the realities of these women.